TINGKAT EFEKTIVITAS PEMBERIAN REWARD DAN PUNISHMENT BAGI SISWA SDN CILANDAK BARAT 01 PAGI JAKARTA SELATAN UNTUK MENINGKATKAN MINAT BELAJAR PENDIDIKAN AGAMA ISLAM - Miftahuddin (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The objective of this investigation was to assess the effects of incentives and penalties on the academic performance of pupils enrolled at SD Negeri Cilandak Barat 01 Pagi. The study employed a qualitative descriptive methodology, utilizing observation, interviews, and questionnaires as data collection methods. The study was conducted at a public elementary school, specifically Cilandak 01 Pagi, located in the southern region of Jakarta. The findings of the research indicate that the implementation of incentives and sanctions can influence the degree of orderliness and academic drive among students, provided that it is executed in a suitable and fitting manner. Regarding the acquisition of knowledge and the cultivation of self-control, educators employ a system of incentives and consequences to incentivize pupils to adhere to the established regulations and exhibit greater compliance and decorum within the academic setting. It is imperative that educators exercise prudence in administering rewards and punishments, as their actions hold significant sway over the outcomes experienced by students. Rewarding students involves inculcating positive values through habituation and appreciation for their positive actions. Conversely, when students engage in negative behaviors, teachers may administer appropriate disciplinary measures. The purpose of punishment is to deter children from engaging in prohibited behaviors. The educator cautions pupils against replication and elucidates the underlying rationales for its prohibition. In educational practice, the utilization of reward and punishment is employed by educators as a means of reinforcement, serving as a stimulus in the process of instructing students. Teachers provide rewards to students as a means of acknowledging positive behaviors or accomplishments through the presentation of gifts or other forms of recognition. The act of providing incentives is aimed at fostering increased engagement and motivation among children in their endeavors to perform and excel. The act of administering punishment by a teacher to students is typically in response to the commission of violations or errors by said students. The imposition of punishment can lead to remorse and regret among students for their inappropriate behavior. The findings of this study suggest that educators are anticipated to exhibit greater levels of creativity and ingenuity by devising novel methods of incentivization and disciplinary action that can be further refined. Are students expected to maintain discipline and study diligently, regardless of the presence of incentives or penalties.